Efektivitas Komunikasi Interpersonal dalam Meningkatkan Loyalitas Pengunjung Warung Kopi di Banda Aceh (Studi Kasus pada Donya Kupie) - Candra Adi Kurnia (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This study aims to analyse the effectiveness of interpersonal communication in increasing the loyalty of coffee shop visitors in Banda Aceh. Using a descriptive qualitative approach, this study explores the experiences and perspectives of coffee shop visitors and staff regarding interpersonal communication that occurs in their interactions. The results of the study indicate that effective interpersonal communication, which includes friendly greetings, personal attention, and non-verbal communication such as smiling and eye contact, has a significant influence on customer satisfaction. Coffee shop owners and management play an important role in creating an environment that supports positive interpersonal communication. These findings provide practical implications that coffee shops in Banda Aceh, by prioritizing good interpersonal communication, can improve customer experience and strengthen their loyalty, which ultimately contributes to business sustainability.